Serologic evidence of the exposure of small mammals to spotted-fever Rickettsia and Rickettsia bellii in Minas Gerais, Brazil - Marcella Gonçalves Coelho; Vanessa do Nascimento Ramos; Jean Ezequiel Limongi; Elba Regina Sampaio de Lemos; Alexandro Guterres; Sócrates Fraga da Costa Neto; Tatiana Rozental; Cibele Rodrigues Bonvicino; Paulo Sérgio D'Andrea; Jonas Moraes-Filho; Marcelo Bahia Labruna; Matias Pablo Juan Szabó (Journal of Infection in Developing Countries)
Introduction: Sources of pathogenic Rickettsia in wildlife are largely unknown in Brazil. In this work, potential tick vectors and seroreactivity of small mammals against four spotted-fever group Rickettsia (R. rickettsii, R. parkeri, R. amblyommii and R. rhipicephali) and Rickettsia bellii from peri-urban areas of Uberlândia, a major town in Brazil, are described for the first time.